The effects of physical exercise on Cardiac Endurance among smokers - JIBI PAUL,; KHAIRUL NIZAM BIN ABDUL RAHMAN, (International Journal of Pharma and Bio Sciences, 2017)
Smoking is fumes of inhalation and exhalation from burning tobacco in cigarettes. It is one of the biggest cause of death and illness in UK. The negatives effects of tobacco also include poor physical and cardiovascular endurance, poor physical performance and increased rates of injury and complications from physical activity. Cardiorespiratory endurance exercise helps the body become more efficient and better able to cope with physical challenges. Objective of the study was to find out the effects of physical exercise on cardiac endurance among smokers. This study was a Randomize Controlled Trial (R.C.T). Forty (40) subjects of smokers from KPJ Healthcare University College were selected for the study and randomly divided into two equal groups. The first 20 participants were in experimental group whereas the next 20 participants were in control group. Harvard Step Test used to identify the cardiovascular endurance among the subjects before and after the exercise program. Experimental group was trained with specific physical exercise program for 2 weeks but the control group was not given any specific exercise during the period of study. Fitness Index Score used to measure the outcome of the subjects. The outcome of cardiac endurance improved significantly in experimental group greater than the control group (p<0.005). The study concluded that physical exercise can improve cardiac endurance in smokers. Abbreviations: HR- Heart Rate, RHR- Resting Heart Rate, FIS- Fitness Index Score.